Sistem Pendeteksi Kebocoran Liquified Petroleum Gas (LPG) Menggunakan Sensor MQ-2 Berbasis Mikrokontroler - Garonga, Melki; Michael, Aryo; Dudung, Marni (Publikasi dan UKI Press UKI Toraja., 2021)
Liquified Petroleum Gas (LPG) is a household need which is currently the most widely used by the community as a fuel other than petroleum. The use of LPG cylinders, which increases every year, is directly proportional to the increased risk of fire caused by gas leaks. Many LPG cylinders circulating in the community today do not use good safety. Therefore, a tool is needed to detect LPG leaks so that people can find out more quickly when there is a gas leak. This system is designed using a microcontroller-based MQ-2 sensor. The MQ-2 sensor functions as a gas leak detector, the buzzer serves as a warning in the event of a gas leak and the SIM800L will send an SMS via the user's smartphone. The MQ-2 sensor can detect gas leaks at a distance of 2 meters in a closed room without ventilation. The MQ-2 gas sensor detects gas leaks using a distance that can be influenced by room temperature and the sensitivity of the MQ-2 sensor, so that the MQ-2 sensor produces a non-permanent time even though it is at the same distance. The buzzer sounds when the MQ-2 sensor detects a gas leak. SIM800L can send SMS notifications to smartphones of LPG cylinder owners when the MQ-2 sensor detects a gas leak, but the time it takes to send an SMS is not fixed because it is influenced by whether the network used by the simcard on the smartphone or the simcard on the SIM800L is good or not.